2020
DOI: 10.7759/cureus.10064
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up Study of Changes in Prostaglandin-Associated Periorbital Syndrome After Switch From Conventional Prostaglandin F2alfa to Omidenepag Isopropyl

Abstract: Background Cosmetic problems induced by conventional prostaglandin F2α (PGF2α) analogs are common. We prospectively evaluated the improvement of patients with prostaglandin-associated periorbital syndrome (PAPS) for whom the treatment regimen was switched from conventional PGF2α analogs to a new selective prostaglandin-EP2 agonist (i.e., omidenepag isopropyl). Methods We finally evaluated 12 patients with follow-up for one year who changed the therapy from conventional PGF2α drugs to omidenepag isopropyl. Digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…An extension of this study, in 12 patients with PAP syndrome who were switched to omidenepag isopropyl 0.002%, found that, after 12 months, deepening of the upper eyelid sulcus improved in six patients, flattening of the lower eyelid bags improved in three, upper eyelid ptosis improved in two, and eyelid hyperpigmentation improved in three [60]. All six patients with improved deepening of the upper eyelid sulcus had been previously receiving bimatoprost or travoprost.…”
Section: Omidenepag Isopropyl -Global Clinical Development Program and Real-world Datamentioning
confidence: 80%
“…An extension of this study, in 12 patients with PAP syndrome who were switched to omidenepag isopropyl 0.002%, found that, after 12 months, deepening of the upper eyelid sulcus improved in six patients, flattening of the lower eyelid bags improved in three, upper eyelid ptosis improved in two, and eyelid hyperpigmentation improved in three [60]. All six patients with improved deepening of the upper eyelid sulcus had been previously receiving bimatoprost or travoprost.…”
Section: Omidenepag Isopropyl -Global Clinical Development Program and Real-world Datamentioning
confidence: 80%
“…Omidenepag is a selective prostaglandin EP2 receptor agonist with a nonprostaglandin structure that reduces the IOP by increasing the outflow facility and the uveoscleral outflow 5,9 . It has been previously reported that the IOP-lowering effect of omidenepag was comparable to that observed for latanoprost 0.005% in patients with OHT or POAG 5,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Although prostaglandin F2α analogs (PGF2α) have been widely used as a first-line treatment for glaucoma 1 , a new antiglaucoma eye drop, omidenepag isopropyl 0.002% ophthalmic solution (omidenepag, EYBELIS®; Santen Pharmaceutical Co., Ltd., Osaka, Japan), which is a selective prostaglandin E2 receptor 2 (EP2) agonist, became available for the treatment of glaucoma and ocular hypertension (OHT) in Japan starting in 2018 [5][6][7][8][9][10] . A previous study reported that omidenepag was not inferior to latanoprost 0.005% for the reduction of IOP in patients with OHT or POAG 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atopic dermatitis is probably the most common dermatosis associated with POH [3]. Several medical drugs may cause POH, such as prostaglandins or imatinib [4,5]. A cross-sectional study among Malaysian Chinese identified single nucleotid polymorphism in p53 and vascular endothelial growth factor A (VEGFA) genes.…”
Section: Introductionmentioning
confidence: 99%